Fostering Social Entrepreneurs Through Community Service Programs - Syaripudin, M A; Rosul, Ahmad; Fisabilillah, Malik Rahman; Febriyani, Tini; Putri, Pupu Amelia; Alfarizi, Kgs M; Azzahra, Venny; Andari, Alice Widya; Nurhayati, Nurhayati; Rahmalia, Shinta (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
KKN, as a form of community service in implementation, is carried out in Bumi Asih Village, Palas District, aiming to foster and develop the community's potential to become social entrepreneurs through various series of activities starting with discussions about local business management, business assistance, and product development. This activity aims to increase the community's ability to manage businesses towards independence. The method applied is the ABCD (Assets-Based Community Development) method. Therefore, community service activities like this need to continue to be pursued to have a long-term impact by improving the village economy, community independence, and changes in community behavior towards a better and more productive life. The program's results show an increase in existing micro businesses, increased community income, and the development of superior products in Bumi Asih Village. Therefore, it can be said that community service activities like this need to continue to be pursued to have a long-term impact in the form of improving the village economy, community independence, and changes in community behavior towards a better and more productive life.